2007
DOI: 10.1038/sj.ejcn.1602706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary intervention with different pre- and probiotics on intestinal bacterial enzyme activities

Abstract: Objective: To investigate the influence of different pre-and probiotics on faecal b-glucuronidase and b-glucosidase activity, as one of the claimed beneficial effects of pre-and probiotics is the hypothesis that these substrates are able to reduce the production of toxic and carcinogenic metabolites by suppressing specific enzyme activities in the colon. Setting: Department of Gastrointestinal Research, University Hospital Gasthuisberg, KU Leuven, Belgium. Design and subjects: The effect was evaluated in a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 35 publications
3
37
1
Order By: Relevance
“…Also, prebiotic supplementation significantly decreased the faecal activity of β-glucuronidase, a carcinogen metabolising enzyme, compared to control animals. The same results were described by (Nalini et al 2004;Manju and Nalini 2006;De Preter et al 2008). It has been shown that some polyphenols may also influence bacterial metabolising enzymes and thus influence overall cancer risk.…”
Section: Discussionsupporting
confidence: 74%
“…Also, prebiotic supplementation significantly decreased the faecal activity of β-glucuronidase, a carcinogen metabolising enzyme, compared to control animals. The same results were described by (Nalini et al 2004;Manju and Nalini 2006;De Preter et al 2008). It has been shown that some polyphenols may also influence bacterial metabolising enzymes and thus influence overall cancer risk.…”
Section: Discussionsupporting
confidence: 74%
“…The ability of probiotic strains to restore or maintain the composition of the microbiota may help prevent inflammatory immune signaling induced by dysbiosis. Probiotic administration has been shown to limit dysbiosis in many disease states, including colitis models, and to restore a normal microbiota composition more quickly than with placebo (289)(290)(291). Patients with minimal hepatic encephalopathy secondary to cirrhosis who were treated with LGG showed significantly increased prevalences of Lachnospiraceae and Clostridia cluster XIV and decreased prevalences of Enterobacteriaceae and Porphyromonadaceae relative to placebo-treated controls (292).…”
Section: Protective Mechanisms Of Probiotics Against Ulcerative Colitismentioning
confidence: 99%
“…In a human volunteer study with oligofructose-enriched inulin de Preter et al (2007de Preter et al ( , 2008a showed that together with an increase in faecal bifidobacteria, the production of colonic ammonia and p-cresol was reduced.…”
Section: Changes In Faecal Metabolites and Enzyme Activitymentioning
confidence: 99%